2021
DOI: 10.1002/ajmg.a.62393
|View full text |Cite
|
Sign up to set email alerts
|

Physical therapy treatment of hypermobile Ehlers–Danlos syndrome: A systematic review

Abstract: Physiotherapy techniques are regularly prescribed in the hypermobile type Ehlers-Danlos syndrome (hEDS) and they are appreciated by the patients. The objective of this systematic review was to investigate the effect of the different physiotherapy techniques related to the children and adult patients with hEDS. PubMed, SPORTDiscus, Cochrane Library, PEDro, Scopus, and Embase databases were analyzed from inception to April 2020. Characteristics of the studies (authors), patients (sample size, sex, age, Beighton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Long‐term physical inactivity leads to physical deconditioning, 54 including decreased muscle strength and cardio‐respiratory fitness. Despite studies identifying kinesiophobia as a possible barrier to exercise, 53 the mainstay of treatment for HSD/hEDs is exercise and pain management 41 . Literature conveys that these patients already have higher levels of anxiety, 55 which may also have a dysautonomia element with symptoms such as hyperventilation, nausea, and light‐headedness, which are significantly more common in HSD/hEDS patients 56 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long‐term physical inactivity leads to physical deconditioning, 54 including decreased muscle strength and cardio‐respiratory fitness. Despite studies identifying kinesiophobia as a possible barrier to exercise, 53 the mainstay of treatment for HSD/hEDs is exercise and pain management 41 . Literature conveys that these patients already have higher levels of anxiety, 55 which may also have a dysautonomia element with symptoms such as hyperventilation, nausea, and light‐headedness, which are significantly more common in HSD/hEDS patients 56 .…”
Section: Discussionmentioning
confidence: 99%
“… 37 The patient's decreased awareness of her body posture meant she was unable to maintain the position, which decreased her pain; therefore, we wanted to assess to see whether a DEFO, in the form of leggings, which also encompassed the hip and pelvic region, could assist in reducing her sway back posture. Core control, hip, lower limb, breathing, and proprioceptive exercises 41 were tailored to her needs so that they were manageable; paced to accommodate her pain, chronic fatigue, and dizziness; and were relevant to helping her function postoperatively. In a systematic review of exercise programs for hEDS patients, a period of 4–8 weeks was commonly reported in studies.…”
Section: Case History and Examinationmentioning
confidence: 99%
“…Long-term physical inactivity leads to physical deconditioning [54], including decreased muscle strength and cardio-respiratory fitness. Despite studies identifying kinesiophobia as a possible barrier to exercise [53], the mainstay of treatment for HSD/hEDs is exercise and pain management [41]. Literature conveys that these patients already have higher levels of anxiety [55], which may also have a dysautonomia element with symptoms such as hyperventiliation, nausea and light-headedness which are significantly more common in HSD/hEDS patients [56].…”
Section: Discussionmentioning
confidence: 99%
“…The patient's decreased awareness of her body posture meant she was unable to maintain the position which decreased her pain, therefore we wanted to assess to see if a DMO(r), in the form of leggings which also encompassed the hip and pelvic region, could assist in reducing her sway back posture. Core control, hip, lower limb, breathing and proprioceptive exercises [41] were tailored to her needs so that they were manageable; paced to accommodate her pain, chronic fatigue and dizziness; and were relevant to helping her function post-operatively. In a systematic review of exercise programmes for hEDS patients, a period of 4-8 weeks was commonly reported in studies [41].…”
Section: Problem Listmentioning
confidence: 99%
See 1 more Smart Citation